The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1007/s11249-009-9497-4
|View full text |Cite
|
Sign up to set email alerts
|

Geometric Shape Effects of Surface Texture on the Generation of Hydrodynamic Pressure Between Conformal Contacting Surfaces

Abstract: Micro-surface texturing design is becoming an important part of surface engineering since engineering practices and analyses have indicated that surface textures may significantly affect the tribological performance of contact interfaces. Advances in the manufacturing technologies of surface finishing and micro-machining, such as laser surface texturing, photolithography, and etching, LIGA process, have made it possible to fabricate different fine structures on various engineering surfaces. Though the influenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
192
1
2

Year Published

2016
2016
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 303 publications
(214 citation statements)
references
References 20 publications
19
192
1
2
Order By: Relevance
“…Several classes of tribological experiments were developed in order to investigate the benefits of laser surface texturing in term of reduction of friction coefficients and reduction of wear rates, mainly on steel surfaces [11][12][13][14][15]. But there is a lack of information about the interaction between laser beam and material structure and the laser beam, which plays a key role in the formation of dimples of required shapes and surface integrity [16].…”
Section: Introductionmentioning
confidence: 99%
“…Several classes of tribological experiments were developed in order to investigate the benefits of laser surface texturing in term of reduction of friction coefficients and reduction of wear rates, mainly on steel surfaces [11][12][13][14][15]. But there is a lack of information about the interaction between laser beam and material structure and the laser beam, which plays a key role in the formation of dimples of required shapes and surface integrity [16].…”
Section: Introductionmentioning
confidence: 99%
“…The results showed the effects of the dimple size and density on the friction reduction were similar to those under the low loading condition [23][24][25]29]. The shape of the dimple, however, was found to have negligible impact on the friction, contradicting the findings of Galda et al [25] and Yu et al [30] where the loads were much lower. Instead of relying on the experimental measurements, Meng et al [34] numerically simulated the friction behavior of parallel surfaces, and found that the effectiveness of micro-dimples on the friction reduction was dependent on both the operating condition and the surface roughness condition.…”
mentioning
confidence: 62%
“…Tang et al [29] demonstrated the strong influence of the adjacent dimple interactions on the hydrodynamic pressure. Yu et al [30] found the geometric shapes and orientations of dimples have an evident impact on the load-carrying capacity, while considering a single dimple instead of a dimple array on the surface. Brunetiere and Tournerie [31] simulated the hydrodynamic lift mechanism of a mechanical seal with textured surfaces, pointing to the importance of the dimple geometry and density in the friction reduction.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Siripuram et al [15] carried out to numerically studied to find that the effect of the triangular dimple orientation on the leakage. Yu et al [16] carried out theoretical studies to investigate the effect of the triangular dimple orientation on the hydrodynamic pressure. Xie et al [17] have investigated tribological performance of triangular dimples in water lubrication by experimental methods.…”
Section: Introductionmentioning
confidence: 99%